Podcasting for Dummies - Morris, Tee, 1968-; Tomasi, Chuck (Tantor Media, Inc., 2021)
Produce a podcast like the pros More people than ever are turning to podcasts for on-demand, mobile entertainment and information. Podcasting For Dummies offers a fast and easy way to get the know-how you need to produce and distribute one of your very own. Written by a pair of podcasting pioneers, this book shares insight on the technology behind recording, editing, and sharing podcasts, along with tips and tricks on how to produce a pro-level podcast. Podcasting has enjoyed a recent boom thanks to a new crop of hit podcasts catching the ears of the public and media along with the continued growth of mobile and streaming devices as a source for entertainment. If you want to jump on the podcasting bandwagon, you've come to the right place! In this fully updated edition, would-be and experienced podcasters alike will get all the tech information, production insight, and promotional tips they need to either get a podcast off the ground or improve on an existing one. - Get the gear you need - Find your podcasting voice - Find and build an audience New tools have made it easier than ever to create a podcast-and this book shows you how.